Listening with the Eyes: The Silent Language of Observation in Case Taking. - Kumar, Manvendra (Homoeopathic Heritage, 2025)
One of the most important, yet frequently undervalued tools in homoeopathic case taking is observation. The body language, posture, gestures, dress, facial expressions and non-verbal clues that convey more information than words are all examined in this article. We explore the ways in which pioneers such as Hahnemann, Boenninghausen, Kent and Hering etc. stressed the practitioner's function as a quiet observer, one who listens with the eyes just as much as the ears, drawing from traditional homoeopathic philosophy and clinical practice. This article highlights the indispensable importance of careful, intuitive observation in identifying the entirety of symptoms and accurately prescribing in a world that is becoming more and more dependent on verbal narratives and technology.